Operative management of tibial plateau fractures: an assessment of functional and radiological outcomes with Rasmusssens scoring system - Subash, Yeshwanth; Dhamu, Ilavarasan M.; B., Jagadeesh; N., Preethi; Jayaram, Manoj; Naidu, Gunalan K. (International Journal of Research in Orthopaedics, 2017)
Background: Fractures of the proximal tibia involve a major weight bearing joint and are intra-articular injuries which frequently result in functional impairment. They require an accurate reduction of the articular surface with stable internal fixation. If these fractures are not managed appropriately, they often result in high rates of morbidity in the form of knee stiffness and arthritis. This study was done to assess the functional and radiological outcomes following various surgical modalities and to compare them with other studies as available in literature. Methods: 30 patients with tibial plateau fractures treated by various surgical modalities at Saveetha Medical College and Hospital were studied from January 2013 to February 2015 and were followed up for a minimum period of 6 months. Functional and radiological outcomes were assessed by the Rasmussens scoring system. Results: All 30 patients fulfilling the inclusion criteria were thoroughly evaluated and were taken up for surgery with various modalities of fixation which included cannulated cancellous screws, T and L buttress plates and locking compression plates. Articular surface elevation with bone grafting was done in depressed fractures. Early knee mobilization was started and strict non-weight bearing walking was advocated. We had a 90% acceptable functional result which was comparable with other studies. Conclusions: In our study, we conclude that accurate reduction of the articular surface with stable internal fixation and early mobilization with bone grafting in depressed fractures with protracted weight bearing till fracture union gives good functional results. Also radiological values often do not often correlate well with functional outcomes.